Hubungan antara Kelas Fungsional Gagal Jantung Kronik dengan Tingkat Keparahan Anemia pada Pasien di Rumah Sakit Atma Jaya - Bryan Nathaniel; Luse Luse; Febie Chriestya; Yunita Maslim (Majalah Kedokteran Indonesia, 2020)
Introduction: There are 40 million people predicted to suffer from heart failure (HF), in Indonesia it is around 13% of the population. The incidence of anaemia in heart failure patients is estimated to be between 17-50%. AnGagal emia is known to increase mortality risk and worsening prognosis in HF patients and a better understanding of the mechanism will lead to better treatment effectiveness.Methods: The study uses analytical observational method and a cross-sectional design. Data are taken from medical records admitted in 2016 to 2018 and grouped based on New York Heart Association Functional Class (NYHA-FC) and anemia severity (WHO anaemia cut-off point). Results: Eighty-one anemic HF patients analyzed and consists of 34,57% NYHA II, 24,69% NYHA III, and 40,7% NYHA IV. A total of 50,6% patients are mildy anemic and 49,4% are moderately anemic. No severe anemia was found. Multivariate analysis shows chronic HF functional class did not have a significant relationship with anaemia severity (p = 0,179). Conclusions: There is no significant relationship between Chronic HF NYHA-FC and anaemia severity. Severe anemia are rarely found in HF patients without severe kidney failure.